2018
DOI: 10.1002/cssc.201800620
|View full text |Cite
|
Sign up to set email alerts
|

Opening Furan for Tailoring Properties of Bio‐based Poly(Furfuryl Alcohol) Thermoset

Abstract: This work shows how furan ring-opening reactions were controlled by polymerization conditions to tune the cross-link density in bio-based poly(furfuryl alcohol) (PFA). The influence of water and isopropyl alcohol (IPA) on the polymerization of furfuryl alcohol, and particularly on furan ring-opening, was investigated by means of C NMR and FT-IR spectroscopy. Results indicated that formation of open structures were favored in the presence of solvents, thus leading to modification of the thermo-mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 44 publications
5
50
0
Order By: Relevance
“…It has been shown that furan ring opening reactions occur preferentially when the polycondensation of FA occurs in water. 9 The same is observed for the peaks at 1372 and 1243 cm −1 . In untreated wood, these peaks correspond respectively to C-H deformation in holocellulose and C-O stretching and CvO deformation in lignin and xylene.…”
Section: Interactions Of Humins or Pfa With Wood Tissuessupporting
confidence: 68%
See 2 more Smart Citations
“…It has been shown that furan ring opening reactions occur preferentially when the polycondensation of FA occurs in water. 9 The same is observed for the peaks at 1372 and 1243 cm −1 . In untreated wood, these peaks correspond respectively to C-H deformation in holocellulose and C-O stretching and CvO deformation in lignin and xylene.…”
Section: Interactions Of Humins or Pfa With Wood Tissuessupporting
confidence: 68%
“…These ring opening reactions can occur in the presence of water during wood treatment thus leading to the increase in the signal of these open structures as already observed for the neat PFA resin. 9 In humin modified wood, the formation of hemiacetal functions as the result of crosslinking between aldehydes and hydroxyls from wood components might also occur. Indeed, the FTIR signature from hemiacetals appears between 1360 and 1400 cm −1 (ref.…”
Section: Interactions Of Humins or Pfa With Wood Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furfuryl alcohol undergoing a controlled furan ringopening reaction can be tuned to produce tailor-specific materials, with very impressive properties, which can find targeted industrial applications [97]. This argument is further supported by the studies of Iroegbu et al [69], who demonstrated in their work, that due to the complex reaction that furfuryl alcohol can undergo during a polymerisation reaction, in varied reaction conditions, it has the potential to transfer or carry-over its monomeric functionality to the oligomeric and even, the polymeric states.…”
Section: Selected Uses/applicationsmentioning
confidence: 99%
“…These side reactions may have a significant impact on the final polymer structure. Indeed, opening furan rings during the FA polymerization, leads to a lower final crosslinking density by decreasing Diels-Alder reaction, resulting on direct impact on the mechanical properties of the final polymer [26]. Furthermore, obtaining these opened furan structures is amplified by the addition of protic polar solvents suggesting disruption mechanisms of FA polymerization.…”
Section: Introductionmentioning
confidence: 99%